A mutation in desmin makes skeletal muscle less vulnerable to acute muscle damage after eccentric loading in rats. Issue 9 (19th August 2021) - Langer, Henning T.; Mossakowski, Agata A.; Avey, Alec M.; Wohlgemuth, Ross P.; Smith, Lucas R.; Zbinden‐Foncea, Herman; Baar, Keith
Abstract: Desminopathy is the most common intermediate filament disease in humans. The most frequent mutation causing desminopathy in patients is a R350P DES missense mutation. We have developed a rat model with an analogous mutation in R349P Des . To investigate the role of R349P Des in mechanical loading, we stimulated the sciatic nerve of wild‐type littermates (WT) (n = 6) and animals carrying the mutation (MUT) (n = 6) causing a lengthening contraction of the dorsi flexor muscles. MUT animals showed signs of ongoing regeneration at baseline as indicated by a higher number of central nuclei (genotype: P  < .0001). While stimulation did not impact central nuclei, we found an increased number of IgG positive fibers (membrane damage indicator) after eccentric contractions with both genotypes (stimulation: P  < .01). Interestingly, WT animals displayed a more pronounced increase in IgG positive fibers with stimulation compared to MUT (interaction: P  < .05). In addition to altered histology, molecular signaling on the protein level differed between WT and MUT. The membrane repair protein dysferlin decreased with eccentric loading in WT but increased in MUT (interaction: P  < .05). The autophagic substrate p62 was increased in both genotypes with loading (stimulation: P  < .05) but tended to be more elevated in WT (interaction: P  = .05). Caspase 3 levels, a central regulator of apoptotic cell death, was increased with stimulation in both genotypes (stimulation: P  < .01) but more so in WT animals (interaction: P  < .0001). Overall, our data indicate that R349P Des rats have a lower susceptibility to structural muscle damage of the cytoskeleton and sarcolemma with acute eccentric loading.